2022
DOI: 10.3390/rs14040928
|View full text |Cite
|
Sign up to set email alerts
|

Can GPM IMERG Capture Extreme Precipitation in North China Plain?

Abstract: Extreme precipitation events (EPE) often cause catastrophic floods accompanied by serious economic losses and casualties. The latest version (V06) of the Integrated Multi-satellite Retrievals for Global Precipitation Measurement (GPM IMERG) provides global satellite precipitation data from 2000 at a higher spatiotemporal resolution with improved quality. It is scientifically and practically important to assess the accuracy of the IMERG V06 in capturing extreme precipitation. This study evaluates the two widely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Several studies have confirmed the ability of IMERG to reproduce the global spatial characteristics of precipitation fields on annual and seasonal scales [15][16][17]. However, spaceborne precipitation estimates at shorter timescales, particularly in the case of heavy rainfall events, pose more challenges, with a general tendency to underestimate [13,[17][18][19][20][21][22]. In addition, despite the large amount of work aimed at evaluating IMERG in different regions around the world, the authors of [23] reviewed a number of limitations, gaps, and suggestions provided in recent studies.…”
Section: Introductionmentioning
confidence: 93%
“…Several studies have confirmed the ability of IMERG to reproduce the global spatial characteristics of precipitation fields on annual and seasonal scales [15][16][17]. However, spaceborne precipitation estimates at shorter timescales, particularly in the case of heavy rainfall events, pose more challenges, with a general tendency to underestimate [13,[17][18][19][20][21][22]. In addition, despite the large amount of work aimed at evaluating IMERG in different regions around the world, the authors of [23] reviewed a number of limitations, gaps, and suggestions provided in recent studies.…”
Section: Introductionmentioning
confidence: 93%
“…To establish the credibility of the simulation before analyzing the physical processes based on the simulation output, we use the IMERG-Final Run (V06 version) data product as rainfall observation to evaluate the WRF model's simulation performance concerning the precipitation in Liaoning Province. The IMERG products have the advantage of higher temporal (half-hourly) and spatial resolution (0.1 • ) compared to low density and uneven spatial distribution ground-based observations in the regions with complex terrain [50]. Therefore, using high-resolution satellite-derived precipitation datasets can well reflect the precipitation situation and identify rainfall characteristics in the vicinity of Changbai Mountain.…”
Section: Limitations Of the Researchmentioning
confidence: 99%
“…IMERG is a US GPM Science Team precipitation product that applies intercalibrated estimates over various international constellations of precipitation satellites and conducts monthly surface precipitation gauge analyses to compute higher temporal (half-hourly) and spatial (0.1 • × 0.1 • ) resolutions [43,44]. These characteristics of IMERG precipitation products are advantageous in extreme studies of precipitation globally [21].…”
Section: Global Precipitation Measurement (Gpm) Missionmentioning
confidence: 99%
“…The European Space Agency's Sentinel-1 Synthetic Aperture Radar (SAR) and Sentinel-2 optical multispectral satellites are becoming popular data sources for effective flood monitoring [20]. Flood mapping using the Sentinel data are mostly conducted in northern temperate latitudes such as Europe, the UK and Canada [21]. In tropical areas, cloud cover is a prevalent issue in optical satellite imagery [22].…”
Section: Introductionmentioning
confidence: 99%